Morphometry and Pollution Load Capacity of Lake Pondok Lapan in Langkat Regency, North Sumatra - Muhtadi, Ahmad; Yunasfi, Yunasfi; Marufi, M.; Rizki, A. (Oseanologi dan Limnologi di Indonesia, 2017)
Morphometry is necessary to know the physical characteristics of a lake and how much the ability of the lake to receive pollutant loads. Determination of water quality status and pollution load capacity of lake water is very important to do with the utilization of lake by the community for cultivation activity of floating net cage (KJA). This study aimed to determine the characteristics of morphometry and bathymetry of the lake, determine the status of water quality and the capacity of lake pollution load. The study was conducted in JanuaryâMarch 2015. Mapping was done by making a path of 100 trajectories which was then processed with ArcView. The observation station for water quality consisted of 4 stations. The status of water quality was determined by the Pollution and Storage Index method based on PerMen LH. No. 115 of 2003. The capacity of lake pollution loud refers to PerMen LH. 28 of 2009. The results showed that Lake Pondok Lapan area reached 63,472.78 m2 (6.35 ha) with a maximum depth of 4.15 m. This lake is classified as a closed water, aerobic, with a residence time of 11â12 days. The depth of compensation is at a depth of 2.61â2.85 m. The water discharge coming out of the lake ranges 12,963.45â14,111.71 mÂ³ per day. The status of water quality of Lake Pondok Lapan is categorized as uncontaminated with score 0 for the Storet method and 0.46â0.86 for Pollution Index method. Lake pollution load capacity is of 1.98 kg of phosphorus per year.